Digital Project Development Study: How Does Scratch Accommodate Students' Numeracy and Logical Thinking Skills? - Ummah, Siti Khoiruli; Effendi, Moh Mahfud; Rosyadi, Alfiani Athma Putri (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2025)
Numeracy and logical thinking skills need to be accommodated in lectures, especially logic and algorithm lectures. The purpose of this study is to develop a digital project-based lecture design assisted by the Scratch Application to accommodate students' numeracy and logical thinking skills. The research method uses the ADDIE (Analysis, Design, Develop, Implementation, Evaluation) development model with 20 students as trial subjects. The research instruments used were observations of the implementation of the lecture model and the provision of tests so that the data analysis technique used was using inferential statistical tests to see the effectiveness of the lecture model compared to the lecture model using the discussion method. The results of the study showed a digital project in the form of making simple animations in the form of games by applying mathematical logic rules when compiling scripts. The use of branching and looping algorithms is able to accommodate students' abilities in logical thinking so that there is a systematic thinking pattern. In conclusion, the digital project-based lecture design assisted by Scratch has significant differences with the lecture model using the discussion method based on students' numeracy and logical thinking skills.